Diagnóstico da agricultura de precisão no sudoeste do estado de Goiás - Soares Filho, Romeu (2014)
The precision agriculture (PA), initiated in Brazil at the end of the last century is considered as the newest management tool of agricultural activity, also has in Brazilian Savanna soils, where soil and climate conditions are favorable to the development of cultures, a perfect field for its development. There are, however, in the region lack of information about the State of the art of this new technique, already in use by farmers. With this, the aim of this work was to carry out the adoption analysis and use of this technology in the southwest of Goiás State, with real information of intensity, ways of use and the conditions of its adoption. Therefore, was applied between June 2012 and July 2013, a questionnaire to producers who use some form of precision agriculture, researching in this technology, problems, sources of information and difficulties with the new technology. Together with the questionnaires, were made evaluations about the quality and distribution of correctives and fertilizers at broadcasting, with producers who agree with the evaluation. There was analyzed the longitudinal and transversal distribution of granulated fertilizers, limestone, gypsum and magnesium oxide made with centrifugal spreaders, in real conditions of each property. Considering the parameters analyzed, it was concluded that the technique of precision agriculture in the micro region is in the early stages of adoption. Soil sampling grid and broadcasting fertilization are the most applied technologies. The use of sensors and precision irrigation are technologies still absents in the micro region. The main information sources about AP are agricultural consulting companies and fairs of the region. The main obstacles mentioned were lack of skilled labor and AP equipment costs. However, the producers stated that they intend to expand the use of the AP techniques. The broadcasting spread of fertilizers and correctives by centrifugal spreader, which are the most used equipment in the studied region, were not uniform along the applied area. It is necessary to search alternative to this equipment for the quality distribution, within the AP principles.